2021
DOI: 10.1111/pim.12839
|View full text |Cite
|
Sign up to set email alerts
|

Th1/Th2/Th17 cytokine profile in hepatic cystic Echinococcosis patients with different cyst stages

Abstract: Cystic Echinococcosis (CE), a global parasitic zoonosis, is caused by infection with the larval stage of tapeworm Echinococcus granulus sensu lato (E. granulosus s.l.) and remains to be a significant public health issue, which also causes huge economic losses annually due to its worldwide distribution. 1 Humans are one of the intermediate hosts, and their infection may occur through accidental consumption of embryonated eggs or direct contact with infected definitive hosts. 2 Hydatid cysts mainly develop in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…In the present work, we have shown that a variety of infiltrating inflammatory cells and fibroblasts gathered surrounding hydatid lesions in the liver of CE patients, producing an immune microenvironment between the LL of the tapeworm and normal hepatic tissue ( Figure 1A ). Histologically, immune microenvironment formation and persistent liver fibrosis may have contributed to the control of parasite overgrowth ( Yasen et al., 2021a ). Our results demonstrated that local immune response patterns and the specific infiltrating immune cell profiles of CE patients were altered during disease progression and varied across patients ( Ahn et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work, we have shown that a variety of infiltrating inflammatory cells and fibroblasts gathered surrounding hydatid lesions in the liver of CE patients, producing an immune microenvironment between the LL of the tapeworm and normal hepatic tissue ( Figure 1A ). Histologically, immune microenvironment formation and persistent liver fibrosis may have contributed to the control of parasite overgrowth ( Yasen et al., 2021a ). Our results demonstrated that local immune response patterns and the specific infiltrating immune cell profiles of CE patients were altered during disease progression and varied across patients ( Ahn et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the infection progresses, a permanent T1-type response follows (high levels of IFN-γ and IL-17A) by 8 weeks, which limits the growth of established cyst forms in the liver in the murine model. Moreover, the T17-type response also plays complementary roles to the T1-type response in protective immunity against helminth infection ( Yasen et al., 2021a ). This is consistent with reports from Dematteis, S., who found that early type-2 cytokines were induced by E. granulosus s.s. in favor of parasite establishment, since type-2 cytokines are involved in mediating inhibition of macrophage activation ( Dematteis et al., 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Th2 cells secrete type 2 cytokines (IL-4), which assist to escape parasites in the late stages. 28,29 The ELISA, ELISPOT, and flow cytometry data in this study showed that rEg.P29 T+B immunization could effectively stimulate Th1 cytokine production in mice, and the IgG typing assay suggested that rEg. P29 T+B elicited a Th1-T cell response.…”
Section: Discussionmentioning
confidence: 67%
“…CD4 + T cells can differentiate into different helper T cell subtypes, Th1 cells secrete type 1 cytokines (IFN‐γ), which protect the body in the early stages of infection and stimulate CD8 + T cell proliferation. Th2 cells secrete type 2 cytokines (IL‐4), which assist to escape parasites in the late stages 28,29 . The ELISA, ELISPOT, and flow cytometry data in this study showed that rEg.P29 T+B immunization could effectively stimulate Th1 cytokine production in mice, and the IgG typing assay further suggested that rEg.P29 T+B elicited a Th1‐biased T cell response.…”
Section: Discussionmentioning
confidence: 68%
“…The P29 is encoded by a single gene in the Echinococcus genus and has been applied as a potential serological marker for the post-treatment monitoring of CE (19). Consistent with previous descriptions of other vaccines, the protection produced by rEg.P29 was dominated by a Th1 response (20)(21)(22). However, the underlying mechanism of rEg.P29 has remained ambiguous.…”
Section: Introductionmentioning
confidence: 99%